Army recruitment video advertisements in the US and UK since 2002: Challenging ideals of hegemonic military masculinity?. (March 2021) - Jester, Natalie
This article examines video recruitment advertising for the US and UK armies between 2002 – post 9/11 – and 2018 in order to unpack constructions of gender in a context of what has been called a military recruitment crisis. The findings suggest that the recruitment crisis has made possible some interesting representations of gender in the armies of the respective states. The US constructs its army in less traditionally masculine terms: women and people of colour are frequently present as equal team members and there is a focus on emotional as well as physical strength. In contrast, UK advertising pre-2012 does not feature many women, presenting them in subordinate terms, and focuses on risk-taking and physical strength. After this period, however, there is a marked change and British army advertisements begin to look more like those produced by the US. The author argues that this represents a rejection of hegemonic military masculinity and that such a rejection functions to obscure military violence by presenting armies as progressive.